Ag substituted Au clusters supported on Mg-Al-hydrotalcite for highly efficient base-free aerobic oxidation of 5-hydroxymethylfurfural to 2, 5-furandicarboxylic acid. Issue 22 (1st November 2022) - Liu, Zongyang; Tan, Yuan; Li, Jie; Li, Xiuli; Xiao, Yan; Su, Juan; Chen, Xingkun; Qiao, Botao; Ding, Yunjie
Abstract : A highly active and selective Au20 Ag/MgAl-300 catalyst was developed for HMF oxidation to FDCA under base-free reaction conditions using molecular oxygen as the oxidant, with high conversion of HMF (100%) and high yield of FDCA (>95%). Abstract : Aerobic oxidation of 5-hydroxymethylfurfural (HMF ) to 2, 5-furandicarboxylic acid (FDCA ) is a promising alternative route to produce renewable biodegradable plastics, which has stimulated intense interest in recent years. Supported gold catalysts have shown great potential for this reaction, but the selectivity and stability need to be improved. In addition, the requirement for base additives makes the process less effective and sustainable. Herein, highly active and selective Au–Ag bimetallic nanoclusters supported on MgAl-hydrotalcite (HT) were developed for HMF oxidation to FDCA under base-free reaction conditions using molecular oxygen as the oxidant. The presence of small amounts of Ag (0.034–0.065 wt%) in Au25 clusters greatly enhanced the catalytic reaction rates and selectivity for HMF tandem oxidative steps, leading to both high conversion of HMF (>97%) and high yield of FDCA (>95%). Besides, the catalyst stability was also enhanced by the addition of Ag. The characterization results suggested that the substitution of Ag atoms modified the electronic structure of Au while likely maintaining the primary geometry. Thus, a significant synergistic effect could be observed over trace Ag modified Au–Ag bimetallic nanoclusters. The present work provides new insight into the alloying effect, and helps understand highly efficient Au-based catalysts for aerobic oxidation of biomass derived molecules under base-free conditions.